2021
DOI: 10.3390/curroncol28010052
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch Repair Universal Screening of Endometrial Cancers (MUSE) in a Canadian Cohort

Abstract: Background: Approximately 2–6% of endometrial cancers (ECs) are due to Lynch Syndrome (LS), a cancer predisposition syndrome caused by germline pathogenic variants (PVs) affecting the DNA mismatch repair (MMR) pathway. Increasingly, universal tissue-based screening of ECs has been proposed as an efficient and cost-effective way to identify families with LS, though few studies have been published on Canadian cohorts. The purpose of this study was to evaluate the feasibility and overall performance of a universa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 46 publications
0
9
1
Order By: Relevance
“…The patients’ demographic characteristics were similar to those of other populations of patients with endometrial cancer. 10 12 , 15 , 17 , 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients’ demographic characteristics were similar to those of other populations of patients with endometrial cancer. 10 12 , 15 , 17 , 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of Lynch syndrome in our population is similar to that in a previously described US population 15 , 16 but, interestingly, is less than half that reported in a cohort of Montréal patients. 17 At the time of writing, germline status remained unknown for 91 of the 189 participants eligible for genetic counselling. Our criteria for referral to medical genetics were broader than those in the studies by Hampel and colleagues 15 and Lawrence and colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…The likelihood of EC in women suffering from Lynch syndrome is between 40 and 60% [ 31 ]. In another study conducted in Canada, it was reported that Lynch syndrome was diagnosed in 6.4% of EC patients over the age of 70 [ 32 ].…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Screening individuals for LS genetic testing based on clinical criteria was important as an inexpensive approach to detect patients at risk on a population scale. However, this screening method relies on accurate information about cancer prevalence in pedigrees to estimate their risk of being families with LS (LAWRENCE et al, 2021). Moreover, screening approaches based on clinical criteria were found to have low sensitivity, with half of CRC-associated LS cases being missed, which required new methods to identify suspected LS in the genetic testing .…”
Section: Universal Screening Of Tumorsmentioning
confidence: 99%
“…In 2009, the American working group named Evaluation of Genomic Applications in Practice and Prevention (EGAPP) recommended screening all CRC for detecting LS (EGAPP, 2009). Currently, the universal use of tumor screening by either MSI or IHC for all newly diagnosed CRC and EC is highly recommended by several international institutions (DI MARCO et al, 2018;GIARDIELLO et al, 2014;JU et al, 2018;LAWRENCE et al, 2021;LEE et al, 2020;SYNGAL et al, 2015). In addition to CRC and EC, some authors also support universal screening in other LS-associated tumors, including ovarian, urinary, and sebaceous tumors (KUNNACKAL JOHN et al, 2022).…”
Section: Universal Screening Of Tumorsmentioning
confidence: 99%